Clinical neurophysiology. (August 2020) - Fowle, Adrian J.
Abstract: Clinical neurophysiology is a diagnostic discipline concerned with measuring electrical activity in the central nervous system, peripheral nervous system and muscle. Patients of all ages and severities of condition are referred by many different specialties in primary and secondary care. Three main categories of investigation are offered, each of which has basic and more advanced tests. Electroencephalography (EEG) is usually a recording of cortical activity. Its principal use is in managing epilepsy, particularly in classification; it has an increasing role in assessing disorders of consciousness and other brain disorders. Nerve conduction and electromyography (EMG) studies are primarily tests of peripheral nervous system and muscles, and are often lumped together as 'EMG'. They are most sensitive to focal and systemic disorders of large fibre peripheral nerves. They have a lesser role in small fibre neuropathy, radiculopathy and muscle disease. Evoked potentials are a small and specialized category with a variety of infrequently used but important tests. Understanding in which cases neurophysiology can help and the effect on the patient is key to a proper collaboration between clinical neurophysiology and referring departments. There are few adverse effects or contraindications.